Ghond the Hunter - Mukerji, Dhan Gopal, (Brill | Manohar Publishers & Distributors, 2024)
Ghond the Hunter is based on the story of a 15-year-old boy Ghond and his training as a hunter, the festivals, and customs in which he participates, and his keen observation of wildlife. The book covers mannerisms, customs, themes associated with the countryside, festivals, flora, and fauna (especially wild animals), and the issue of rite of passage. This book is arranged in lyrical form, where the story brings out the close relationship of humans and animals. It is helpful to understand India from an anthropological point of view.